Efficacy of High-volume Evacuator in Aerosol Reduction: Truth or Myth? A Clinical and Microbiological Study - Hitesh Desarda; Abhijit Gurav; Chandrakant Dharmadhikari; Abhijeet Shete; Subodh Gaikwad (Tabriz University of Medical Sciences, 2014)
Background and aims. Basic periodontal treatment aims at eliminating supra- and sub-gingival plaque and establishing conditions which will allow effective self-performed plaque control. This aim is primarily achieved with sonic and ultrasonic scalers. However, generation of bacterial aerosols during these procedures is of great concern to patients, the dentist and the dental assistant. The aim of this study was to compare the reduction in aerosol with and without high-volume evacuator through a microbiological study. Materials and methods. For this clinical study a fumigated closed operatory was selected. Maxillary incisors and canines were selected as an area for scaling. Piezoelectric ultrasonic scaling was performed in the absence and in the presence of a high-volume evacuator at 12 and 20 inches from the patient's oral cavity. In both groups scaling was carried out for 10 minutes. Nutrient agar plates were exposed for a total of 20 minutes. After this procedure, nutrient agar plates were incubated in an incubator at 37°C for 24 hours. The next day the nutrient agar plates were examined for colony forming units by a single microbiologist. Results. The results showed no statistically significant differences in colony forming units (CFU) with and without the use of a high-volume evacuator either at 12 or 20 inches from the patient's oral cavity. Conclusion. It was concluded that high-volume evacuator, when used as a separate unit without any modification, is not effective in reducing aerosol counts and environmental contamination.